Medical follow-up and long-term survival of patients with cerebrovascular accident: data from the REGION-M registry - S. N. Tolpygina; M. I. Chernysheva; A. V. Zagrebelny; V. P. Voronina; N. P. Kutishenko; N. A. Dmitrieva; O. V. Lerman; Yu. V. Lukina; M. M. Lukyanov; E. Yu. Okshina; N. E. Parsadanyan; S. Yu. Martsevich; et al. (Российский кардиологический журнал)
Aim. To assess the survival rate of patients after cerebrovascular accident (CVA), depending on the visits to the local outpatient clinic and the type of medical supervision, and in the first year after hospital discharge.Material and methods. The outpatient part of the REGION-M registry included 684 patients assigned to the City Polyclinic № 64 of Moscow, discharged from the F. I. Inozemtsev City Clinical Hospital (Moscow) in the period from January 1, 2012 to April 30, 2017 with a confirmed diagnosis of cerebral stroke/transient ischemic attack.Results. During the first year after the CVA, 451 (65,9%) patients visited the local clinic on their own (group 1), while 166 (24,3%) patients was consulted by house call (group 2), and 67 (9,8%) did not see the physician (group 3). Patients visited by house call were more likely to have prior coronary artery disease and stroke, and the age of men was older than in other groups. Patients who did not see a doctor were less likely to have comorbidities and disabilities, and were less likely to visit the clinic before stroke. The mortality of patients in group 3 was significantly higher throughout the entire follow-up period (55,2%, 70,1% and 77,6% at stages 1, 2 and 3 (p<0,001), respectively) than in group 2 (31,2%, 55,4% (p<0,001)) and group 1 (23,7%, 37,0% and 54,3% (p<0,001)). Mortality of patients in group 1 was lower than group 2 (p<0,05-0,01). The relative risk of death in clinic visitors was 0,450 (95% confidence interval (CI), 0,333-0,608, p<0,0001), while in those visited by a doctor at home — 0,668 (95% CI, 0,482-0,927, p<0,05). In multivariate analysis and adjustment for sex and age (relative risk (RR) of death, 0,08 (95% CI, 0,048-0,133), p<0,0001 and 1,036 (95% CI, 1,031-1,042), p<0,001, respectively), the independent contribution of the factor of clinic visits was preserved. Thus, the RR of death in visitors was 0,996 (95% CI, 0,994-0,999), p<0,001 and 0,998 (95% CI, 0,995-1,0), p<0,05.Conclusion. The lower mortality among those visited the local clinic in the first year after CVA and among those who were visited by a doctor at home, compared with patients who were not observed, confirms the important role of medical supervision in the post-hospital period.